A jornada de uma estudante neurodivergente na licenciatura em matemática: estudos e reflexões - Bernardini, Maiara Araújo (Universidade Federal de São Carlos, 2024)
This work describes the academic journey of the first author in a Mathematics Teaching Degree, emphasizing her experiences as a neurodivergent individual (with Attention Deficit Hyperactivity Disorder, dysorthographia, and dyslexia). At the beginning of the thesis process, due to limited representation and acknowledgment of neurodivergent students in academia, requests were made to adapt institutional policies and structures for accessibility. These requests were approved by higher authorities at the university attended by the first author. Strategies adopted included audio materials and visual aids combined with accessible language. Alongside personal factors, the study drew upon extensive research covering topics such as cognitive skills essential for learning mathematics, and those impacted by ADHD and dyslexia, among other aspects of neurodivergent brain function. Peer-reviewed articles were sourced using Boolean operators across three databases and languages, focusing on publications from 2018 to 2022, excluding grey literature. Key aspects of the author’s life were discussed, including her diagnosis, higher education journey, and strategies to manage challenges. The study also explored microaggressions in academic settings, examining their correlation with math anxiety and promoting Math Resilience as a pivotal concept to shift this perspective. In summary, this work proposes tangible solutions for inclusion and representation of neurodivergent students, emphasizing the importance of understanding cognitive skills and inclusive teaching strategies for meaningful change.
The journey of a neurodivergent student in a mathematics teaching degree: studies and reflections
Keywords: Neurodivergência; Resiliência matemática; Inclusão acadêmica; Neurodivergence; Mathematical resilience; Academic inclusion; CIENCIAS EXATAS E DA TERRA::MATEMATICA